PENGARUH REWARD, PUNISHMENT DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Irma Andriani (Ensiklopedia Social Review, 2021)
Human resources have a major role in every company activity without the support of reliable human resources, the company's activities will not be completed properly. This study aims to determine how much reward, punishment and work stress on the performance of employees of PT. Pelindo II (company) Teluk Bayur Padang branch using data collection methods through surveys and distributing questionnaires to 91 respondents. There are 91 questionnaires distributed and 78 which can be processed. The analytical method used is regression analysis and correlation analysis. Based on the results of multiple regression analysis obtained the following equation y = 3.433 +0.224X1 + 0.714X2 - 0.017X3 + e. (a) there is a positive and significant effect between reward (x1) on employee performance (y) with tcount 2.750 or the significance level is smaller than alpha (0.007